Cahaya Bebas HR Document Management System - mentri, alvin hawkins; zainal, nurezayana (Applied Information Technology And Computer Science, 2025)
Cahaya Bebas Sdn Bhd, a leader in road construction, resolved inefficiencies caused by traditional, paper-based HR processes by implementing a web-based HR document management system. This system automates tasks such as leave requests, pay slip distribution, and document management. Designed using an object-oriented approach and the prototyping model, it features modules for user login, employee management, leave management, pay slips, and report generation. User Acceptance Testing (UAT) was conducted to ensure the system met operational needs, gathering feedback from end-users for final refinements. Employees now apply for leave and access pay slips online, while HR digitally approves requests and manages records. The system has significantly improved efficiency, reduced paperwork, enhanced data security, and minimized environmental impact. By addressing the challenges of manual processes and geographically dispersed operations, the solution has successfully enhanced productivity and streamlined operations for Cahaya Bebas Sdn Bhd.